2016
DOI: 10.1371/journal.pone.0153869
|View full text |Cite
|
Sign up to set email alerts
|

Mental Representations of Illness in Patients with Gestational Trophoblastic Disease: How Do Patients Perceive Their Condition?

Abstract: BackgroundGestational Trophoblastic Disease comprises a group of benign and malignant disorders that derive from the placenta. Using Leventhal’s Common-Sense Model as a theoretical framework, this paper examines illness perception in women who have been diagnosed with this disease.MethodsThirty-one women diagnosed with Gestational Trophoblastic Disease in a hospital in Italy were asked to complete the Illness Perception Questionnaire-Revised to measure the following: illness Identity, illness opinions and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Regarding the characteristics of mental illness representations, as previously described in Di Mattei et al [16], the statistical analyses show that patients within our sample reported a relatively weak illness Identity: the mean number of symptoms women associated to their disease was in fact rather low. With regard to patients' opinions surrounding their illness, the highest mean scores were found on the Emotional representations and the Treatment control subscales of the questionnaire.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Regarding the characteristics of mental illness representations, as previously described in Di Mattei et al [16], the statistical analyses show that patients within our sample reported a relatively weak illness Identity: the mean number of symptoms women associated to their disease was in fact rather low. With regard to patients' opinions surrounding their illness, the highest mean scores were found on the Emotional representations and the Treatment control subscales of the questionnaire.…”
Section: Discussionsupporting
confidence: 70%
“…The relationship between illness perception and psychological morbidity has never been analyzed in GTD patients; to our knowledge, illness representations have been investigated in this group of patients exclusively in relation to medical and demographic variables [16]. Using this literature as a starting point, we designed an explorative study with the aim of evaluating how patients perceive their illness during the β-hCG follow-up period after GTD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…21 A multidisciplinary approach providing education and support has been recommended for both GTD and GTN patients. 8,9,20 Our sample of GTN survivors, with high levels of anxiety surrounding their ß-hCG surveillance, was more in favor of professional counseling than our low-worry group.…”
Section: Discussionmentioning
confidence: 90%
“…[6][7][8][9] This is a problem based on recent research indicating differences between GTN and benign GTD, 8,9 although these study cohorts had short follow-ups (1-36 months) and small sample sizes of GTN patients (n = 8-17). 9 It is important to understand the impact of ß-hCG monitoring in GTN survivors using a larger sample size and broader range of follow-up and examine how it relates to mental wellness to comprehend the meaning of survivorship for these women. Our cohort consists of women diagnosed with GTN and treated with chemotherapy at a cancer center.…”
Section: Introductionmentioning
confidence: 99%
“…This result underlines the importance of including a supportive care component in the clinical management of these women: this would help patients develop a more positive mental representation of illness and avoid quality of life and relationship disruption. 7,21 Although nonYstatistically significant, patients in the high-risk group showed a reduced pregnancy rate compared with the low-risk group (57.1% vs 36.4%, P = 0.06). Remarkably, when excluding patients receiving hysterectomy for resistant disease, no difference in pregnancy rate could be detected between the 2 groups (57.1% vs 52.2%, P = 0.449).…”
Section: Discussionmentioning
confidence: 91%